The central role of natural killer cells in preeclampsia - Wei, Xiaoqi; Yang, Xiuhua (Frontiers in Immunology, 2023)
Preeclampsia (PE) is a disease that is unique to pregnancy and affects multiple systems. It can lead to maternal and perinatal mortality. The precise etiology of PE is unclear. Patients with PE may have systemic or local immune abnormalities. A group of researchers has proposed that the immune communication between the fetus and mother is primarily moderated by natural killer (NK) cells as opposed to T cells, since NK cells are the most abundant immune cells in the uterus. This review examines the immunological roles of NK cells in the pathogenesis of PE. Our aim is to provide obstetricians with a comprehensive and updated research progress report on NK cells in PE patients. It has been reported that decidual NK (dNK) cells contribute to the process of uterine spiral artery remodeling and can modulate trophoblast invasion. Additionally, dNK cells can stimulate fetal growth and regulate delivery. It appears that the count or proportion of circulating NK cells is elevated in patients with or at risk for PE. Changes in the number or function of dNK cells may be the cause of PE. The Th1/Th2 equilibrium in PE has gradually shifted to an NK1/NK2 equilibrium based on cytokine production. An improper combination of killer cell immunoglobulin-like receptor (KIR) and human leukocyte antigen (HLA)-C may lead to insufficient activation of dNK cells, thereby causing PE. In the etiology of PE, NK cells appear to exert a central effect in both peripheral blood and the maternal-fetal interface. To maintain immune equilibrium both locally and systemically, it is necessary to take therapeutic measures directed at NK cells.